COMPARATIVE STUDY OF THE WAGE RATE OF RURAL AND URBAN FEMALE WORKERS - PRABHAKAR KUMAR (International Journal of Multidisciplinary Research and Studies, 2020)
The proportion of the population that is actively looking for work in India is influenced by economic, social, cultural, and demographic processes. In the Indian National Sample Survey that was conducted in 1999/2000, measures of employment, unemployment, and unpaid labour were all taken. The official labour force participation rate for males was 85%, but the rate for women was just 35%. Since 1989, there has been a general trend towards a lower rate of female involvement in the labour force. In addition, problems with measurements cast doubt on the veracity of the reported rates of change for women's self-employment. The job that women conduct in the home and on farms can sometimes be argued to qualify as independent contractor work. On the other hand, a significant number of women identify themselves as housewives. According to the data, there is a U-shaped relationship between female employment and educational levels. There is presented here a comprehensive analysis of not only domestic work but also other forms of unpaid labour as well. Women who identify as belonging to the Muslim cultural group perform more work outside the home (and are more likely to identify as belonging to the category of 'inactive') than women who identify as belonging to other cultural groups. The presence of economic deprivation makes finding work more likely. We present a variety of explanations that assist explain both the work patterns and the housewifization trend. These reasons are interrelated. These include things like personal preferences as well as things like the local economy and population.